Faire écouter la littérature avec les yeux - Sylvie Ducas (Itinéraires)
This article aims to examine three very different approaches of writers using their site as a building space for expressing their ethos inseparable from a very specific use of Web 2.0. Éric Chevillard’s writing workshop, the performative space of Chloé Delaume and Régine Detambel’s advertising showcase illustrate in fact, various postures of the writer at work. If the book and the library continue to found the authorial posture and writing gesture, the writer speaks about himself and makes himself public in a new way, driven by digital devices.